DEVELOPMENT OF LOCAL HEALTHY FOOD, LINKING THAILAND-CHINA-MALAYSIA TO PROMOTE THE ECONOMY OF THE SOUTHERN BORDER COMMUNITY - RAKSUDJARIT, Sukrita; NAMBURI, Nantharat; PHINICHCHAN, Ganyarat; KAEWFAI, Jenta; PHONGKRAPHAN, Nattharawee; JIANCHATCHAWANWONG, Siriwan; JUNCHAIRUSSAMEE, Shinnawatra (Asian Administration and Management Review, 2024)
This research aims to develop and improve the local healthy food, linking Thailand-China-Malaysia. The populations and key informants include those with low income and livelihood in the specified sub-district areas of Betong, Yala, Thailand, totaling 260 individuals. Thirteen individuals were interviewed. Data was collected from research documents and fieldwork information, employing a focus group and questionnaire method. It was done to develop local healthy food that would link Thailand, China, and Malaysia to enhance the economy of southern border communities in Yala. The data analysis involved qualitative information, and descriptive statistics were used for quantitative analysis. The study result indicated that the development of local healthy food for the three targeted sub-districts had a likeness to the developed local healthy food recipes for all nine items, which included Kao Mok, Ba Jang Neramit, Bua Loy, Pak Nam Betong Tod Krob Kua Kratiam, Kangsom Planil Sai Nam Lai Dok Da La, Nasi Kabu Kampong Sauce Budu Subparod, Mee Betong Pad Kreaung Kang Peenang Hoi Krang Sod, Kai Betong Neung See Ew Hed Hom, and Kang Kai Dam Sayo.